MODELING ON THYROID DIAGNOSIS USING MACHINE LEARNING APPROACHES – A REVIEW - DEEPTHI GURRAM,; M. R. NARASINGA RAO, (International Journal of Pharma and Bio Sciences, 2016)
Diagnosis is a crucial task in bioscience attributable to its criticality, potency and accuracy in determining whether or not a patient encompasses a specific illness. This shall decide the foremost appropriate line of treatment. The diagnosis naturally may be a complicated and a fuzzy cognitive technique, and soft computing ways, like neural networks, has shown nice potential to be applied within the development of the medical support systems (MDSS). There has been an outsized increase within the range of thyroid cases over the past few years. Since thyroid encompasses a complicated relation with metabolism and weight, it's extraordinarily necessary to diagnose thyroid disease as early as attainable. Diagnosis of thyroid disease is one among the necessary problems to develop a medical decision support system which is able to facilitate the physicians to require effective decisions. This paper presents Associate in nursing complete survey of work done in the past with relation to thyroid disease diagnosis. A survey on completely different computing ways employed by researchers for the applying of diagnosis or predicting thyroid illness is mentioned during this paper.